If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 11 = -2 + 7y Reorder the terms: 11 + -4y = -2 + 7y Solving 11 + -4y = -2 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 11 + -4y + -7y = -2 + 7y + -7y Combine like terms: -4y + -7y = -11y 11 + -11y = -2 + 7y + -7y Combine like terms: 7y + -7y = 0 11 + -11y = -2 + 0 11 + -11y = -2 Add '-11' to each side of the equation. 11 + -11 + -11y = -2 + -11 Combine like terms: 11 + -11 = 0 0 + -11y = -2 + -11 -11y = -2 + -11 Combine like terms: -2 + -11 = -13 -11y = -13 Divide each side by '-11'. y = 1.181818182 Simplifying y = 1.181818182
| a-78=-2a+10 | | 2=1-4 | | 1/2x+1/3=1/4x-5/12 | | X^4-4x-5=0 | | y-18=35x | | X*X-2X+7=42 | | 30x=75+12y | | x=50+16x | | f(x)=5x-10 | | 7x+5=2x+13 | | 3(7+7)=68 | | (4x-50)+(x+60)=180 | | 2[2+3(y+1)]=22 | | 6(2b+6)=96 | | 7-x=56 | | (12x+4y)+(43x+35y)= | | 14=-8-5b+2 | | 16-(2-3b)+4b= | | 5x-11=3(2x-5) | | 6a+(4-3a)+4= | | 4x+20=-x+50 | | 11x-13=5x-55 | | (x-4)5=70 | | 2(4x-3)+2x=114 | | 3x-2-2x=-5 | | 1296=4x-3 | | x^3+3mx^3+2(6m-7)x+10m-6=0 | | 4x+3y-2=0 | | 5(4+2n)-(8n-12)=68 | | 5y^5-5y^4-10t^3=0 | | -6q^3+28q^2+10q=0 | | 3.4x-5.4=27.62 |